The mediating effect of innovation on the relationship between managerial ability and competitive advantage of Bandar Lampung MSMEs - Eka Travilta Oktaria; Pungky Nanda Raras; Iskandar Ali Alam; Andala Rama Putra Barusman; Habiburrahman Habiburrahman (Goodwood Publishing, 2025)
Purpose: This study aims to analyze the effect of managerial ability on competitive advantage through innovation among MSMEs in the craft sub-sector of Bandar Lampung City. Methodology/approach: The study employed a quantitative approach using the survey method. The population of this research consisted of all 62 MSMEs in the craft sub-sector in Bandar Lampung City, while a sample of 60 MSMEs was selected through random sampling. Data were collected from the owners and managers of these MSMEs. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS version 3.2.9 to examine the relationships between variables, both directly and through the mediating effect of innovation. Results/findings: The study shows that managerial skills have a direct positive and significant influence on competitive advantage. Furthermore, managerial skills also have a positive influence on innovation, and innovation acts as a partial mediator that strengthens the influence of managerial skills on competitive advantage. These findings emphasize the importance of effective and innovative managerial development in enhancing the competitiveness of MSMEs. Conclusion: Managerial capability is a strategic resource that plays a direct and indirect role through innovation in creating competitive advantage. Integrating managerial management and innovation is a key strategy for MSMEs to maintain and enhance competitiveness in the market. Limitations: This study focused exclusively on MSMEs in the craft sub-sector of Bandar Lampung City; therefore, the findings may not be generalizable to other MSME sectors or regions. Furthermore, the variables examined were limited to managerial ability, innovation, and competitive advantages. Contribution: This study reinforces the Resource-Based View and Dynamic Capabilities theories in linking managerial ability, innovation, and competitive advantage, providing practical insights for MSME managers to strengthen managerial competence and foster innovation for enhanced organizational competitiveness.